SOCIAL RELATIONSHIPS, NEIGHBORHOOD DISORDER, AND COGNITIVE DECLINE IN ELDERLY: DIFFERENCES BY LIVING ARRANGEMENT. (16th November 2018) - Hu, Y; Seo, D; Shih, P; Lin, H
Abstract: The majority of studies of social relationships and cognitive function have focused on the general older population regardless of their living arrangements. Given that older adults living alone (OALA) are more likely to be isolated from social network and formal sources of support than those who reside with others (non-OALA), investigating whether the roles of social relationships in cognitive function of older adults differ by living status is needed to better inform tailored interventions targeted at OALA. Further, little is known about how perceived neighborhood safety and trust of older adults are associated with the trajectory of cognitive function. Using multilevel modeling with data of adults over 65 years from the Health and Retirement Study, this study investigated whether the longitudinal associations of neighborhood disorder and subjective/objective social isolation with cognitive function differ by older adults' living arrangements. Analyses were conducted on two subsets of 3, 455/1, 142 older adults who resided with others/lived alone from 2006 to 2016(2016 data released recently), respectively. Neighborhood disorder (non-OALA: β=-0.10; OALA: β=-0.12; both ps<.01) was associated with a decline in cognitive function regardless of living arrangements. Having friends (β=0.84, p<.01), frequently meeting with friends (β=0.19, p<.01) and positive support from children (β=0.41, p=.02) were related to retaining the cognitive function of OALA but not that of non-OALA. Comparing to non-OALA, maintaining the friendship is important to protect the cognitive function of OALA. Future aging-in-place interventions that prevent decline in cognitive function of OALA should enhance neighborhood safety and trust as well as strengthen community bonding.